Comparative assessment of gaseous fuel emission - Levytska, Olena Hryhoriivna; Voytenko, Yulia Vladimirovna; Orishechok, Anastasiia Oleksiivna (Національний технічний університет "Харківський політехнічний інститут", 2021)
The work presents estimated comparative assessment of emissions release in combustion products during work of high–power steam boilers with the use of traditional fuel –natural gas and alternative fuels – blast–furnace and coke–oven gases generated in the process of technological cycle at iron and steel and coke–chemical enterprises. Calculation algorithm is shown and formulas for assessment of carbon content in exhaust gases are defined, conclusions on ecological efficiency of gaseous fuels are given. The purpose of the work was to evaluate the emissions of harmful substances generated during the combustion of natural, blast furnace and coke oven gases, justification of the calculation of carbon content of a given chemical composition and determine the optimal environmental impact of analogues of natural gas. The comparative estimation of pollutant emissions into atmospheric air during combustion of natural, coke oven and blast furnace gases revealed: –high sulfur dioxide emissions from combustion of blast furnace and coke oven gases due to the presence of sulfur compounds in the composition of these gases; –relatively high emissions of nitrogen compounds for natural and coke oven gases and relatively low emissions for blast furnace gas; – сarbon emissions are high for all types of fuels which have been considered, most carbon dioxide gets into the air when burning natural gas, least – when burning blast furnace gas; –significantly higher methane emissions are observed during the combustion of natural and coke oven gases, respectively, smaller – for blast–furnace gas combustion; –coke oven and natural gases are characterized by low mercury emissions. Comparative assessment of the calculated values of hazardous substances emissions in the combustion products in the process of combustion of natural, coke–oven and blast–furnace gases shows that even at lower working heat of combustion values the coke–oven and blast–furnace gases can compete with natural gas. For the first time, a comparative characterization of the emissions of harmful substances in the combustion of natural, coke oven and blast furnace gases is presented, and it is shown that the gases used in coke and metallurgical industries, which are used as analogues of natural, are logical to use, but require the installation of treatment systems. The paper defines a formula for calculating the carbon content in natural gas from the Urengoy–Uzhhorod gas pipeline. The provided calculations and the introduction of simplified formulas serve as an example for the calculation of emission factors and emissions in assessing the level of safety of existing equipment and can be used in the development of permit documents of enterprises that carry out emissions of harmful substances to the environment.

В роботі приведена розрахункова порівняльна оцінка викидів шкідливих речовин у продуктах згоряння при роботі високопотужних парових котлів із використанням традиційного палива – природного газу та альтернативних палив – доменного та коксового газів, що утворюються в ході технологічного циклу на металургійних та коксохімічних підприємствах. Показаний алгоритм розрахунку та визначені формули для оцінки вмісту вуглецю у вихідних газах, наведені висновки щодо екологічної ефективності газоподібних палив. Метою роботи стала оцінка викидів шкідливих речовин, що утворюються в ході спалювання природного, доменного та коксового газів, обґрунтування розрахунку вмісту вуглецю у паливі заданого хімічного складу та визначення оптимального з точки зору впливу на довкілля аналогів природного газу. При порівняльній розрахунковій оцінці викидів забруднюючих речовин в атмосферне повітря при спалюванні природного, коксового та доменного газів виявлено: – високий викид діоксиду сірки при спалюванні доменного та коксового газів із–за наявності сполук сірки у складі цих газів; – порівняно високі викиди сполук азоту для природного і коксового газів і порівняно низькі – для доменного газу; – викиди сполук вуглецю є високими для всіх розглянутих видів палив, найбільше сполук вуглецю потрапляє в повітря при спалюванні природного газу, найменше – при спалюванні доменного газу; – значно більший викид метану спостерігається при спалюванні природного і коксового газів, відповідно менший – при спалюванні доменного; – коксовий та природний газ характеризуються незначними викидами ртуті. Порівняльна оцінка розрахункових значень викидів забруднюючих речовин у продуктах згоряння в процесі спалювання природних, коксових та доменних газів показує, що навіть при нижчих робочих теплотах спалювання коксовий та доменний гази можуть конкурувати з природним газом. В роботі вперше наведена порівняльна характеристика викидів шкідливих речовин при спалюванні природного, коксового та доменного газів та показано, що отримані на коксохімічному та металургійному виробництвах гази, котрі використовуються як аналоги природного, є логічними у використанні, але потребують встановлення очисних систем. В роботі визначена формула для розрахунку вмісту вуглецю у природному газі із газопроводу Уренгой–Ужгород. Наведені розрахунки та введення спрощених формул слугують прикладом для розрахунку коефіцієнтів емісії та викидів при оцінці рівня безпеки діючого устаткування та можуть бути використаними при розробці дозвільних документів підприємств, що здійснюють викиди шкідливих речовин у довкілля.
Порівняльна оцінка викидів продуктів згоряння газоподібних палив в атмосферне повітря
Keywords: greenhouse gases; hazardous substances; emission indexes; combustion; парникові гази; шкідливі речовини; показники емісії; спалювання